Optimal Clinical Timelines - A Consensus from the Academic Department of Military Surgery and Trauma. Issue 4 (1st December 2009) - Tai, NRM; Brooks, A; Midwinter, M; Clasper, JC; Parker, PJ
Abstract : There are no published studies directly addressing the issue of what is an acceptable timeline from point of wounding to surgical intervention within the military context. The proximal threshold has previously been determined by personal opinion, tactical, logistic and practical imperatives rather than by clinical demands. The aimof this paper is to review all relevantmilitary and civilian studies where timelines have been quoted and to reach a number of unambiguous consensus statements to state the perceived ideal upper limits from point of wounding to holistic and realistic surgical care in modern war. An injured casualty should be transferred to an appropriate surgeon in an appropriate facility in as short a time from wounding as practical. It is clear that the best trauma surgery is performed in large, well resourced, well-supplied, airconditioned hospitals. Current advances aimed to stretch timelines from wounding to surgical intervention are exciting and hold potential but remain scientifically unproven and are currently without any firm evidence base. Further critical research is therefore necessary. The effect of pre-hospital haemostatic resuscitation, provided by the enhanced Medical Emergency Response Team (MERTe) on patient outcome and effective timelines is currently unknown and unproven: it does have intuitive medical merit. There is also a very significant moral and morale component. MERTe serves two main functions; reduction in time from point of wounding to advanced / haemostatic resuscitation and provision of in-flight diagnostics. Continuation of in-flight resuscitation then allows physician-led decision making on critically unstable casualties. This allows either an expedited straight move from the HLS direct to the operating theatre or direct transfer to a regional neurosurgical centre. To prevent avoidable death, our unequivocal conclusion is that there must be an upper limit of 2 hours from wounding to surgical intervention (surgical haemorrhage control) for all casualties.